2022
DOI: 10.37897/rjn.2022.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation in neuromuscular disease with acute respiratory failure: A narrative review

Abstract: Acute respiratory failure (ARF) is a life-threatening condition that often results from the acute onset of neuromuscular disease (NMD) and often coexists with other cardiorespiratory conditions. For more than two decades, existing studies have shown that non-invasive ventilation (NIV) is the main ventilatory support and provides a good clinical outcome in ARF with various conditions, but its use in NMD patients with ARF is still limited. In patients with ARF, NIV can be initiated in fully awake patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated associations among reduced oxygen saturation, increased glucose levels, and elevated respiratory rate on admission with an unfavourable outcome in patients with COVID-19 [41][42][43][44]. RR was found to be an important parameter for predicting ARF in COVID-19 pneumonia patients within 72 hours.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated associations among reduced oxygen saturation, increased glucose levels, and elevated respiratory rate on admission with an unfavourable outcome in patients with COVID-19 [41][42][43][44]. RR was found to be an important parameter for predicting ARF in COVID-19 pneumonia patients within 72 hours.…”
Section: Discussionmentioning
confidence: 91%